Antimicrobial potential of bacteria associated with seagrass from Pantai Samudera Indah waters - Yuli, Yulianti; Idiawati, Nora; Sofiana, Mega Sari Juane (Dept. Marine Science, 2018)
This study aims to obtain bacterial isolates, antimicrobial activity, characterization and identification of bacteria associated with seagrass from the Pantai Samudera Indah waters. To obtain bacterial isolates, the isolation method was carried out. Antimicrobial activity test using the cross streak method. Characterization and identification of bacteria using the Bergey book's Manual Determinative Bacteriology. The results showed that bacterial isolates associated with seagrass from Pantai Samudera Indah waters were 9 isolates. The best antimicrobial activity is Y06 isolate which can inhibit Staphylococcus aureus, Vibrio cholerae, Pseudomonas aureginosa, Esherichia coli, Salmonella typhimurium. Y06 isolates are gram positive, non motile, catalase, urease, oxidase positive, can ferment glucose, mannitol and fructose. Y06 isolates belong to the genus Brevibacterium.